Demon pojednania. Dyskurs o współczesnych Sprawiedliwych w powieści popularnej - Tomczok, Marta (Zagłada Żydów. Studia i Materiały, 2016)
The author analyzes depictions of the Righteous in several Polish popular novels and the accompanying discourse on rescuing. She proves that in popular fiction such depictions dominate over the reckoning discourse, connected with the Polish shared responsibility for the Holocaust. Tomczok analyzes the reasons for that dominance, referring to the Philo-Semitic violence category described by Elżbieta Janicka and Tomasz Żukowski. She devotes special attention to Maja Wolny’s novel Czarne liście and the controversy over the presentation of the pogrom in Kielce, and, first and foremost, this book’s dependence on the scholarly achievements of the scholars affiliated with the Center for Holocaust Research.